How User Group Identity Formation and Maintenance Are Embedded in a Larger Project’s Identity - Emmanuel Nyameke; Harri Haapasalo; Kari-Pekka Tampio (International Journal of Management, Knowledge and Learning)
Purpose: This study explores how the identity of a user group consisting of interface stakeholders is formed and maintained within a larger project.